2014
DOI: 10.1371/journal.pone.0092392
|View full text |Cite
|
Sign up to set email alerts
|

Keeping Your Eyes Continuously on the Ball While Running for Catchable and Uncatchable Fly Balls

Abstract: When faced with a fly ball approaching along the sagittal plane, fielders need information for the control of their running to the interception location. This information could be available in the initial part of the ball trajectory, such that the interception location can be predicted from its initial conditions. Alternatively, such predictive information is not available, and running to the interception location involves continuous visual guidance. The latter type of control would predict that fielders keep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…During interception, subjects tracked visible targets with smooth pursuit eye movements most of the time as reflected by the small gaze-target angle. This is consistent with previous studies on locomotor interception (e.g., Oudejans et al, 1999;Postma et al, 2014). Similarly, in accordance with previous studies (e.g., Land & Lee, 1994), gaze behavior and steering behavior were coordinated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…During interception, subjects tracked visible targets with smooth pursuit eye movements most of the time as reflected by the small gaze-target angle. This is consistent with previous studies on locomotor interception (e.g., Oudejans et al, 1999;Postma et al, 2014). Similarly, in accordance with previous studies (e.g., Land & Lee, 1994), gaze behavior and steering behavior were coordinated.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that actors' gaze is predominantly anchored on the target during both manual interception (e.g., Brenner & Smeets, 2011;Cesqui, Mezzetti, Lacquaniti, & d'Avella, 2015;Lopez-Moliner & Brenner, 2016) and locomotor interception (e.g., McBeath, Shaffer, & Kaiser, 1995;Oudejans, Michaels, Bakker, & Davids, 1999;McLeod, Reed, & Dienes, 2006;Postma, den Otter, & Zaal, 2014). Specifically, to catch a fly ball in a short duration between 1.8 and 2.5 s, actors visually track the ball most of the time (Oudejans et al, 1999;Postma et al, 2014). Interestingly, a recent study in highly trained cricket players has suggested that batters coupled the rotation of their head to the movement of the ball while gaze anticipated the ball's position (Mann, Spratford, & Abernethy, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, a fielder must be able to perceive whether his or her current locomotor efforts are sufficient for keeping constant d (tan α)/dt. When fielders track the ball with their gaze (see Oudejans et al, 1999; Postma et al, 2014), the elevation angle α equals the gaze angle. In this case, gaze angle can be the basis for using the Chapman strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Not only locomotor behavior appears to be in line with the OAC strategy, also gaze behavior fits the use of optical acceleration. It has been shown that participants maintain continuous visual contact with the ball while running to make a catch, even for balls that fly overhead (Oudejans et al, 1999; Postma et al, 2014). Such gaze behavior fits naturally with the use of the OAC strategy, as it implies continuous visual control of interception.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation tried to determine if the initial moments would be essential or if it would be necessary to observe the ball either continuously or for a longer time to conclude if it was reachable or not. Despite the study being inconclusive, one envisages the possibility of achieving tangible results with better structured investigations and a higher number of participants being analysed 28 . Based on these preliminary investigations the present study may be considered a groundbreaking one, once one acknowledges that the use of the Mobile Eye Tracking for the investigation of matters concerning (bio)ethics is still incipient.…”
Section: Resultsmentioning
confidence: 99%